Green Policy-Based Sustainable Development through the Development of Village-Owned Enterprises (BUMDes) - Febrina Rury; Marta Auradian; Amin Raja Muhammad; Hadi Sofyan; Ferlan Margina; Mento Meris Essio (E3S Web of Conferences)
This article is motivated by the innovation of the Siak District government through Regional Regulation No. 4 of 2022 concerning Siak Green District. Siak Green District is implemented based on the principles of a. justice; b. preservation and sustainability; c. participatory; d. local wisdom; e. good governance; and f. community welfare. In achieving the goals of green siak and sustainable development, one of them requires a strategy to optimize the role of village owned enterprises (BUMKam) in promoting the development of Green Siak in Siak District. The locus of this research is Pusako Subdistrict, based on the Siak Road Map Towards Green District, which is a conservation zone, food crop zone, plantation and forestry zone and regional settlement zone. The method used is qualitative with explorative type. The results showed that the management of BUMKam has not been optimal in supporting the green Siak policy as seen from the principle of cooperative, participatory, emancipative, transparent, and sustainable. in addition to the problem of corporate legality and developing businesses that have not been able to raise the potential of the village, and the products of village groups and communities based on Siak Green Policy.